1990
DOI: 10.1007/bf00857661
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic arterial calcification of infancy: a case with prolonged survival

Abstract: We describe a patient with idiopathic arterial calcification of infancy and the following unusual features of the disease: (1) prolonged survival until age 11 years, (2) discordance between the extent of vascular calcification and clinical manifestations of arterial luminal occlusion, (3) a large area of myocardial calcification, (4) symptoms of cerebral-vascular insufficiency, and (5) spontaneous resolution of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The efficacy of bisphosphonates as compared to the spontaneous evolution of the disease is difficult to evaluate. Long-term survival has been reported in patients receiving no specific antimineralization therapy [8,11,24,26], suggesting that spontaneous resolution of calcifications may also occur. In a retrospective study, bisphosphonate therapy was associated with survival in 11 of 17 treated patients, compared to 8 of 26 untreated patients [20].…”
Section: Discussionmentioning
confidence: 95%
“…The efficacy of bisphosphonates as compared to the spontaneous evolution of the disease is difficult to evaluate. Long-term survival has been reported in patients receiving no specific antimineralization therapy [8,11,24,26], suggesting that spontaneous resolution of calcifications may also occur. In a retrospective study, bisphosphonate therapy was associated with survival in 11 of 17 treated patients, compared to 8 of 26 untreated patients [20].…”
Section: Discussionmentioning
confidence: 95%
“…Patients may present with failure to thrive, hypertension, myocardial infarctions and convulsions. Cerebral vascular insufficiency may cause cerebral infarctions [5,12,13]. Periarticular calcifications are a well-known feature in IIAC [1,7]; these appear to be localised in the ligaments [6,14].…”
Section: Discussionmentioning
confidence: 97%
“…There are reports in the literature of long-term survival with resolution of calcification associated with bisphosphonate treatment [Meradji et al, 1978;Van Dyck et al, 1989;Rutsch et al, 2000] but there are also reports of spontaneous resolution of calcification [Marrott et al, 1984;Ciana et al, 2006;van der Sluis et al, 2006] and of fatal outcome despite treatment [Stuart et al, 1990]. Arterial stenosis due to intimal proliferation may also occur in areas devoid of calcification [Witzleben, 1970;Thomas et al, 1990] and persist despite resolution of calcification indicating it may be independent of calcification [Thiaville et al, 1994;Rutsch et al, 2000]. The utility of bisphosphonates for treatment of this condition therefore remains undetermined and they may not alleviate the stenosis.…”
Section: Discussionmentioning
confidence: 88%
“…To date, there are no reports on GACI in heterozygotes; however, an increased risk of myocardial infarction has been reported in individuals carrying the K121Q variant of the ENPP1 gene [Bacci et al, 2005]. Phenotypic variability has been documented with survival into later childhood and rarely adulthood [Marrott et al, 1984;Thomas et al, 1990;Rutsch et al, 2003;Patel et al, 2004;Cheng et al, 2005;Ciana et al, 2006]. Cheng et al reported phenotypic variability in siblings with the diagnosis of GACI and the same compound heterozygous mutations, with the surviving sibling aged 18 months at the time of the report.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation